A SYSTEMATIC REVIEW ON OXALIS CORNICULATA LINN. A CROP FIELD WEED WITH PROMISING PHARMACOLOGICAL ACTIVITIES - MEKAP, SUMAN KUMAR; MISHRA, SAGAR KUMAR; PANDA, PRASANA KUMAR; PANDA, SAGAR SUMAN; SARANGI, DEEPAK KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Various ailments were known to being treated and cured by several herbs either as a main ingredient or being associated with different medical systems. One such clinically significant and endangered crop field weed is Oxalis corniculata Linn. which is generally found in subtropical and tropical regions across the globe. The medicinal significance of this weed is well evidenced in medicinal scriptures such as Ayurveda, Siddha, Unani, and compendiums of India, China, Britain, and America. The present review highlights on some of the crucial phytoconstituents such as flavonoids, tannins, glycosides, and fatty acids isolated from the said plant and their medicinal applications for treating conditions such as inflammation, anxiety, cancer, and diabetes. Further, the review stresses the future scope for therapeutic applications of these specific phytoconstituents of O. corniculata and the need for its research and development.